(untitled) (REMUNOM, 2025)
The main objective of this study is to analyze how supplementary pension plans can help to complement retirement income for a portion of the population. The article begins with a brief historical overview of the emergence and development of Social Security in the world and in Brazil. At the national level, it highlights that the Social Security system is structured around the pillars of Health, Social Assistance, and Social Security. It addresses the pension regimes in Brazil and the main rules for granting retirement by the National Institute of Social Security (INSS), emphasizing the growing deficit of the General Social Security Regime (RGPS), caused by structural problems. It clarifies the main types of private pension plans available for individuals and presents simulations considering various age and income ranges, demonstrating that the earlier a person starts contributing to a supplementary pension plan, the greater the monthly income will be after the accumulation period.